High-rate and high-capacity resin-based hard carbon material as well as preparation method and application thereof
By dispersing carbon nanotubes in resin or resin precursors, high-ratio, high-capacity resin-based hard carbon material is obtained through carbonization treatment, which solves the problem of insufficient conductivity of hard carbon materials, improves the conductivity and capacity of the battery, and extends the Cycling life and reduces calorific value.
Patent Information
- Application Number
- CN202411560998.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-14
AI Technical Summary
The conductivity of hard carbon materials is weak, which leads to a decrease in the rate performance of the battery in the low SOC state, affecting the capacity of the positive electrode material, resulting in a high DC resistance of the battery and a relatively high battery heat generation.
By dispersing the carbon nanotubes in a resin or resin precursor, a high-magnification and high-capacity resin-based hard carbon material is obtained by carbonizing. This method can enhance the conductivity of resin-based hard carbon materials, apply it to the negative electrode of the battery, reduce the AC and DC resistance of the battery, and improve the positive electrode capacity and rate performance of the battery.
It improves the conductivity of the battery, reduces the AC and DC resistance of the battery, improves the positive electrode capacity and rate performance of the battery, extends the cycle life, and reduces the heat generation of the battery.
Smart Images

Figure CN119430132A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hard carbon materials, and in particular to a high-rate and high-capacity resin-based hard carbon material and a preparation method and application thereof. Background Art
[0002] Since the invention of secondary batteries, lithium-ion batteries have made great progress. However, due to limited lithium resources and large price fluctuations due to international geopolitical factors, sodium-ion batteries have developed rapidly in recent years.
[0003] At present, hard carbon is a better negative electrode material for sodium-ion batteries, with advantages such as high capacity and low cost, which can optimize the power of the battery and improve the low-temperature performance of the battery. However, the performance disadvantages of hard carbon also affect the battery. For example, the conductivity of hard carbon is relatively weak, which can easily lead to a decrease in the rate performance of the battery at low SOC, affect the capacity of the positive electrode material, and cause the DC resistance of the battery to be high, and the battery heat generation is relatively high. Summary of the invention
[0004] The main purpose of the present invention is to provide a high-rate and high-capacity resin-based hard carbon material and a preparation method and application thereof, so as to solve the technical problem that the electrical conductivity of the hard carbon material is poor.
[0005] To achieve the above object, the present invention provides a method for preparing a high-rate and high-capacity resin-based hard carbon material, characterized in that the method for preparing the hard carbon material comprises the following steps:
[0006] Dispersing carbon nanotubes in a resin or a resin precursor to obtain a carbon nanotube resin;
[0007] The carbon nanotube resin is carbonized to obtain a high-rate and high-capacity resin-based hard carbon material.
[0008] In some embodiments of the present invention, the carbonization temperature ranges from 800°C to 1500°C.
[0009] In some embodiments of the present invention, the carbonization time is 5 hours to 240 hours.
[0010] In some embodiments of the present invention, the D50 of the high-rate and high-capacity resin-based hard carbon material is in the range of 4 μm to 10 μm.
[0011] In some embodiments of the present invention, the diameter of the carbon nanotubes is 1 nm to 20 nm;
[0012] And / or, the carbon nanotube has a tube length of 3 μm to 20 μm
[0013] In some embodiments of the present invention, the resin includes at least one of phenolic resin, furfural resin, and epoxy resin.
[0014] In some embodiments of the present invention, the mass of the carbon nanotubes is 0.1% to 2% of the total mass of the resin.
[0015] In some embodiments of the present invention, the step of dispersing carbon nanotubes in a resin to obtain a carbon nanotube resin includes: dispersing carbon nanotubes in a resin precursor, and obtaining the carbon nanotube resin through a polymerization reaction.
[0016] In some embodiments of the present invention, the resin precursor includes a phenolic resin precursor, a furfural resin precursor or an epoxy resin precursor.
[0017] In some embodiments of the present invention, the resin precursor includes a phenolic resin precursor, which is obtained by mixing formaldehyde, phenol and a catalyst; or, the resin precursor includes a furfural resin precursor, which is obtained by mixing a furfural raw material and an acid catalyst; or, the resin precursor includes an epoxy resin precursor, which is obtained by mixing bisphenol A, epichlorohydrin and sodium hydroxide.
[0018] The present invention also provides a high-rate and high-capacity resin-based hard carbon material prepared by the preparation method as described above.
[0019] The present invention also provides a use of the high-rate and high-capacity resin-based hard carbon material in a battery.
[0020] The beneficial effects that can be achieved by the present invention are:
[0021] The present invention disperses carbon nanotubes in resin or resin precursor to obtain carbon nanotube resin, that is, the carbon nanotubes can be directly dispersed in the formed resin, and the resin-based hard carbon material can be obtained through carbonization treatment, or the carbon nanotubes can be dispersed in the resin precursor, and the carbon nanotube resin wrapped with carbon nanotubes can be obtained through polymerization reaction of the resin precursor, and then the high-rate and high-capacity resin-based hard carbon material containing carbon nanotubes can be obtained through crushing and carbonization. The doping of carbon nanotubes can enhance the conductivity of the resin-based hard carbon material, and when applied to a battery as an active material in the negative electrode of the battery, the AC resistance and DC resistance of the battery can be reduced, the positive electrode capacity of the battery and the battery rate performance can be improved, and the cycle life can be extended, and the heat generation of the battery can be reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0023] Figure 1 This is a schematic diagram of the preparation process of a high-rate and high-capacity resin-based hard carbon material according to an embodiment of the present invention.
[0024] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0025] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.
[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] In the present invention, descriptions such as "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0028] The present invention provides a method for preparing a high-rate and high-capacity resin-based hard carbon material, referring to Figure 1 , the preparation method of the hard carbon material comprises the following steps:
[0029] S10, dispersing carbon nanotubes in a resin or a resin precursor to obtain a carbon nanotube resin;
[0030] S20. The carbon nanotube resin is carbonized to obtain a high-rate and high-capacity resin-based hard carbon material.
[0031] In some embodiments, dispersing the carbon nanotubes into the resin can be understood as dispersing the carbon nanotubes directly into the already formed resin, for example, dispersing the carbon nanotubes into phenolic resin, furfural resin or epoxy resin, and then tightly wrapping the carbon nanotubes through subsequent carbonization treatment to obtain a resin-based hard carbon material. In this embodiment, the molding resin is in a liquid state, so that the carbon nanotubes are easily mixed evenly.
[0032] In some embodiments, the carbon nanotubes are dispersed in a resin precursor, and the resin precursor can be understood as a reaction system for obtaining a resin through a polymerization reaction, and the reaction system includes reaction raw materials for obtaining the resin through polymerization. Taking phenolic resin as an example, formaldehyde, phenol and a catalyst can be mixed to obtain a resin precursor of the phenolic resin, and the carbon nanotubes are dispersed in the resin precursor, and then a polymerization reaction is carried out. The carbon nanotubes can be tightly wrapped in the structure of the resin and become a part of the resin structure. In the subsequent carbonization process, the carbon nanotubes and the resin are integrated to enhance the rate performance and capacity of the resin-based hard carbon material, while enhancing its strength.
[0033] In some embodiments, the carbonization temperature ranges from 800°C to 1500°C, which can be 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, etc. Under the above carbonization temperature conditions, it is beneficial to promote the carbonization of carbon nanotube resin and obtain high-rate and high-capacity resin-based hard carbon materials.
[0034] In some embodiments, the carbonization time is 5 h to 240 h.
[0035] In some embodiments, carbonization is performed in an inert atmosphere, for example, an argon or nitrogen atmosphere, to prevent the resin from being oxidized.
[0036] In some embodiments, the D50 of the high rate and high capacity resin-based hard carbon material is in the range of 4 μm to 10 μm.
[0037] In some embodiments, the diameter of the carbon nanotubes is 1 nm to 20 nm.
[0038] In some embodiments, the carbon nanotubes have a tube length of 3 μm to 20 μm.
[0039] When carbon nanotubes are dispersed in a resin to obtain a carbon nanotube resin, in some embodiments, the resin includes at least one of a phenolic resin, a furfural resin, and an epoxy resin. Carbon nanotubes can be directly added to the phenolic resin, the furfural resin, and the epoxy resin, and then subsequently carbonized to obtain a high-rate and high-capacity resin-based hard carbon material.
[0040] In some embodiments, after the carbon nanotubes are added to the resin, they are stirred evenly and then carbonized to obtain a high-rate and high-capacity resin-based hard carbon material.
[0041] When dispersing carbon nanotubes in a resin precursor to obtain carbon nanotube resin, in some embodiments, the step of dispersing carbon nanotubes in a resin precursor to obtain carbon nanotube resin includes: dispersing carbon nanotubes in a resin precursor, and obtaining carbon nanotube resin through polymerization reaction.
[0042] In some embodiments, the resin precursor includes a phenolic resin precursor, a furfural resin precursor or an epoxy resin precursor. The above phenolic resin precursor, furfural resin precursor or epoxy resin precursor can obtain the corresponding type of resin through polymerization reaction. Carbon nanotubes are added to the above resin precursors, and then the polymerization reaction is used to make the carbon nanotubes a part of the resin structure, so that the carbon nanotubes and the resin are more firmly combined. In the subsequent carbonization process, the carbon nanotubes and the resin are easily integrated, thereby enhancing the rate performance and capacity of the resin-based hard carbon material, while enhancing its strength.
[0043] Taking phenolic resin as an example, carbon nanotubes are added to the reaction system for preparing phenolic resin, that is, carbon nanotubes are added to the resin precursor of phenolic resin, and the polymerization reaction of phenolic resin is utilized to make the carbon nanotubes a part of the resin structure, so that the carbon nanotubes and resin are more firmly combined. In the subsequent carbonization process, the carbon nanotubes and resin are easily integrated, thereby enhancing the rate performance and capacity of the resin-based hard carbon material, while enhancing its strength.
[0044] In some embodiments, the resin precursor for preparing the phenolic resin includes formaldehyde, phenol, and a catalyst.
[0045] In some embodiments, the catalyst comprises an acidic catalyst comprising at least one of sulfuric acid, phosphoric acid, and hydrochloric acid.
[0046] In some embodiments, the mass ratio of phenol, formaldehyde and catalyst is: 100: (100-150): (0.1-1).
[0047] The particle size of carbon nanotubes is very small and they are easy to agglomerate. The carbon nanotubes can be dispersed first, and then the raw materials required for preparing the resin are added to the system containing the carbon nanotubes.
[0048] In some embodiments, the carbon nanotubes can be first dispersed in an acidic catalyst, such as at least one of sulfuric acid, phosphoric acid and hydrochloric acid. The acidic catalyst can remove impurities on the surface of the carbon nanotubes, increase the functional groups on the surface, improve its dispersibility, and make it more evenly dispersed in the resin precursor, and finally prepare a resin-based hard carbon material with uniform mechanical properties. Then, the acidic catalyst with dispersed carbon nanotubes is evenly mixed with formaldehyde and phenol, and a polymerization reaction is carried out according to the preparation method known in the art to obtain a carbon nanotube resin, that is, a phenolic resin containing carbon nanotubes. In this embodiment, the hydroxyl group of phenol reacts with the aldehyde group of formaldehyde to form phenol hydroxymethyl ether. As the reaction proceeds, these phenol hydroxymethyl ethers can further react with phenolic acid or formaldehyde to form linear oligomers. Under the action of heating and catalysts, the oligomers continue to react to form resins with higher molecular weights. At this stage, the linear polymers can begin to crosslink by forming a second methyl bridge structure. In the process of crosslinking to form phenolic resin, the carbon nanotubes will be tightly wrapped to obtain carbon nanotube resin. The polymerization reaction of phenolic resin is used to make the carbon nanotubes a part of the resin structure, so that the carbon nanotubes and the resin are more firmly combined. In the subsequent carbonization process, the carbon nanotubes and the resin are easy to form an integrated structure, which enhances the rate performance and capacity of the resin-based hard carbon material and enhances its strength. The obtained hard carbon material is applied to the battery as an active material in the negative electrode of the battery, which can reduce the AC resistance and DC resistance of the battery, improve the positive electrode capacity of the battery, the battery rate performance, and can also extend the cycle life and reduce the heat generation of the battery. In addition, carbon nanotubes have extremely high tensile strength and elastic modulus. When combined with hard carbon materials, they can improve the mechanical strength and toughness of hard carbon materials, making them exhibit better stability and durability when subjected to high loads.
[0049] In some embodiments, the carbon nanotubes are dispersed in the acidic catalyst and ultrasonic treatment may be performed to further improve the dispersion.
[0050] Taking furfural resin as an example, carbon nanotubes are added to the reaction system for preparing furfural resin, that is, carbon nanotubes are added to the resin precursor of furfural resin, and the polymerization reaction of furfural resin is utilized to make the carbon nanotubes a part of the resin structure, so that the carbon nanotubes and resin are more firmly combined. In the subsequent carbonization process, the carbon nanotubes and resin are easily integrated, thereby enhancing the rate performance and capacity of the resin-based hard carbon material, while enhancing its strength.
[0051] The resin precursor of the furfural resin of the present invention can refer to the raw materials required for preparing the furfural resin by polymerization reaction in the technical field. Exemplarily, the furfural raw material and the acid catalyst are mixed to obtain the furfural resin precursor, carbon nanotubes are added to the furfural resin precursor, and then the polymerization reaction is carried out according to the reaction conditions in the technical field to obtain the carbon nanotube resin.
[0052] Taking epoxy resin as an example, carbon nanotubes are added to the reaction system for preparing epoxy resin, that is, carbon nanotubes are added to the resin precursor of epoxy resin, and the polymerization reaction of epoxy resin is utilized to make the carbon nanotubes a part of the resin structure, so that the carbon nanotubes and resin are more firmly combined. In the subsequent carbonization process, the carbon nanotubes and resin are easily integrated, thereby enhancing the rate performance and capacity of the resin-based hard carbon material, while enhancing its strength.
[0053] The resin precursor of the epoxy resin of the present invention can refer to the raw materials required for preparing epoxy resin by polymerization reaction in the technical field. For example, bisphenol A, epichlorohydrin and sodium hydroxide are mixed to obtain an epoxy resin precursor, carbon nanotubes are added to the epoxy resin precursor, and then polymerization reaction is carried out according to the reaction conditions in the technical field to obtain carbon nanotube resin.
[0054] In some embodiments, the mass of the carbon nanotubes is 0.1% to 2% of the total mass of the resin or resin precursor, for example, it can be any value in the range of 0.1% to 2%, such as 0.1%, 0.5%, 1%, 1.5%, 2%, etc.
[0055] In some embodiments, after the carbonization treatment is completed, the high-rate and high-capacity resin-based hard carbon material with a desired particle size is obtained by crushing and screening.
[0056] The high-rate and high-capacity resin-based hard carbon material prepared by the preparation method of the present invention can be applied to batteries as an active material in the negative electrode of the battery, which can reduce the AC resistance and DC resistance of the battery, improve the positive electrode capacity of the battery, the battery rate performance, and can also extend the cycle life and reduce the heat generation of the battery. In addition, carbon nanotubes have extremely high tensile strength and elastic modulus. When combined with hard carbon materials, the mechanical strength and toughness of the hard carbon materials can be improved, so that they show better stability and durability when subjected to high loads.
[0057] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following specific embodiments are only used to explain the present invention, and are not used to limit the present invention.
[0058] Example 1
[0059] Example 1 The steps for preparing a high rate and high capacity resin-based hard carbon material are as follows:
[0060] S10. Fully and evenly disperse the carbon nanotubes in hydrochloric acid, add formaldehyde and phenol after ultrasonic dispersion, mix to form a phenolic resin precursor containing carbon nanotubes, and perform polymerization reaction to form a phenolic resin containing carbon nanotubes, wherein the mass ratio of phenol, formaldehyde and catalyst hydrochloric acid in the resin precursor is 100:150:1, and the mass of the carbon nanotubes accounts for 1% of the mass of the resin precursor.
[0061] S20 and carbon nanotube phenolic resin are carbonized at 800°C to 1500°C for 48 hours, cooled to room temperature, and then further crushed and sieved to obtain a high-rate and high-capacity resin-based hard carbon material with a D50 of 4μm to 10μm.
[0062] Example 2
[0063] Example 2 The steps for preparing the high rate and high capacity resin-based hard carbon material are as follows:
[0064] S10, fully and evenly dispersing the carbon nanotubes in the furfural resin to obtain the carbon nanotube furfural resin, wherein the mass of the carbon nanotubes accounts for 1% of the mass of the furfural resin;
[0065] S20 and carbon nanotube furfural resin are carbonized at 800°C to 1200°C for 48 hours, and then cooled to room temperature and further crushed and sieved to obtain a high-rate and high-capacity resin-based hard carbon material with a D50 of 4μm to 10μm.
[0066] Example 3
[0067] Example 3 A high-rate and high-capacity resin-based hard carbon material is prepared by referring to Example 1, except that the added amount of carbon nanotubes is 0.5%.
[0068] Comparative Example 1
[0069] Comparative Example 1: A resin-based hard carbon material is prepared by referring to the preparation method of Example 1, but the difference is that no carbon nanotubes are added in Comparative Example 1.
[0070] Comparative Example 2
[0071] Comparative Example 2: A resin-based hard carbon material is prepared by referring to the preparation method of Example 2, but the difference is that no carbon nanotubes are added in Comparative Example 2.
[0072] Performance Testing
[0073] The O3 phase layered oxide (NaNi 0.33 Fe 0.33 Mn 0.33 O2), conductive carbon black, polyvinylidene fluoride (PVDF), and N-methylpyrrolidone (NMP) were mixed in a ratio of 95:2.5:2.5:66 using a blender to prepare a positive electrode slurry, and then the mixture was heated to 160 mg / cm 2 The surface density is coated on an aluminum foil with a thickness of 16 microns, rolled, and then punched into positive electrode sheets of specified size.
[0074] The hard carbon material prepared in Examples 1 to 3 and Comparative Examples 1 and 2, conductive carbon black, CMC, SBR, and water were mixed in a ratio of 93:2:1.5:3.5:140 using a mixer to prepare a negative electrode slurry, and then heated to 85 mg / cm 2 The surface density is coated on an aluminum foil with a thickness of 16 microns, and after rolling, it is punched into the negative electrode sheet of a high energy density battery of a specified size;
[0075] The positive electrode, separator, negative electrode and separator are stacked together using the lamination method to form a core body. Then, after baking, liquid injection, aging, formation and sealing according to the above steps, a battery with a capacity of about 2.2Ah is formed.
[0076] The performance of the battery was measured and the results are shown in Table 1.
[0077] Table 1
[0078]
[0079] It can be seen from Table 1 that the battery using the high-rate and high-capacity resin-based hard carbon material of Examples 1 to 3 can give the battery higher conductivity, and the positive electrode performance is better than the positive electrode performance of the battery without the high-rate and high-capacity resin-based hard carbon material of the present invention, and the AC internal resistance and DC internal resistance are both small, the cycle performance is high, and the rate retention rate is above 10%, while the comparative example 1 and the comparative example 2 are only 8%. It can be seen that the high-rate and high-capacity resin-based hard carbon material of the present invention is applied to the battery, which can improve the conductivity of the battery, reduce the AC resistance and DC resistance of the battery, improve the positive electrode capacity of the battery, the battery rate performance, and can also extend the cycle life and reduce the heat generation of the battery.
[0080] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a high-rate and high-capacity resin-based hard carbon material, characterized in that: The method for preparing the hard carbon material comprises the following steps: Dispersing carbon nanotubes in a resin or a resin precursor to obtain a carbon nanotube resin; The carbon nanotube resin is carbonized to obtain a high-rate and high-capacity resin-based hard carbon material.
2. The method for preparing a high-rate and high-capacity resin-based hard carbon material according to claim 1, characterized in that: The carbonization temperature range is 800°C to 1500°C; And / or, the carbonization time is 5h to 240h; And / or, the D50 range of the high-rate and high-capacity resin-based hard carbon material is 4 μm to 10 μm.
3. The method for preparing a high-rate and high-capacity resin-based hard carbon material according to claim 1, characterized in that: The diameter of the carbon nanotubes is 1 nm to 20 nm; And / or, the carbon nanotubes have a tube length of 3 μm to 20 μm.
4. The method for preparing a high-rate and high-capacity resin-based hard carbon material according to claim 1, characterized in that: The resin includes at least one of phenolic resin, furfural resin and epoxy resin.
5. The method for preparing a high-rate and high-capacity resin-based hard carbon material according to claim 1, characterized in that: The mass of the carbon nanotubes is 0.1% to 2% of the total mass of the resin or the resin precursor.
6. The method for preparing a high-rate and high-capacity resin-based hard carbon material according to any one of claims 1 to 5, characterized in that: The step of dispersing the carbon nanotubes in the resin precursor to obtain the carbon nanotube resin includes: dispersing the carbon nanotubes in the resin precursor, and obtaining the carbon nanotube resin through a polymerization reaction.
7. The method for preparing a high-rate and high-capacity resin-based hard carbon material according to claim 6, characterized in that: The resin precursor includes a phenolic resin precursor, a furfural resin precursor or an epoxy resin precursor.
8. The method for preparing a high-rate and high-capacity resin-based hard carbon material according to claim 7, characterized in that: The resin precursor includes a phenolic resin precursor, which is obtained by mixing formaldehyde, phenol and a catalyst; Or, the resin precursor includes a furfural resin precursor, and the furfural resin precursor is obtained by mixing a furfural raw material and an acid catalyst; Alternatively, the resin precursor includes an epoxy resin precursor, and the epoxy resin precursor is obtained by mixing bisphenol A, epichlorohydrin and sodium hydroxide.
9. A high-rate and high-capacity resin-based hard carbon material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the high-rate and high-capacity resin-based hard carbon material according to claim 9 in a battery.
Citation Information
Cited By
Melamine and phenolic aldehyde composite resin-based hard carbon microspheres as well as preparation method and application thereof
CN121672486A